Impact of community based nurse-led clinics on patient outcomes, patient satisfaction, patient access and cost effectiveness: A systematic review. (August 2017) - Randall, Sue; Crawford, Tonia; Currie, Jane; River, Jo; Betihavas, Vasiliki
Abstract: Background: The role and scope of nursing practice has evolved in response to the dynamic needs of individuals, communities, and healthcare services. Health services are now focused on maintaining people in their communities, and keeping them out of hospital where possible. Community based nurse-led clinics are ideally placed to work towards this goal. The initial impetus for these services was to increase patient access to care, to provide a cost-effective and high quality streamlined service. Objectives: This systematic review aimed to identify the impact of nurse-led clinics in relation to patient outcomes, patient satisfaction, impact on patient access to services, and cost effectiveness. Methods: A review of community based nurse-led clinic research in Medline, CINAHL and Embase was undertaken using MeSH terms: Nurse-managed centres, Practice, Patterns, Nurse, Ambulatory Care, keywords: nurse-led clinic, nurse led clinic, community and phrases primary health care and primary care. Papers were appraised using the Joanna Briggs Appraisal criteria. Results: The final review comprised 15 studies with 3965 participants. Most studies explored patient satisfaction which was largely positive towards nurse-led clinics. Patient outcomes reported were typically from self-report, although some papers addressed objective clinical measures; again positive. Access was reported as being increased. Cost-effectiveness was the least reported impact measure with mixed results. Conclusions: Nurse-led clinics have largely shown positive impact on patient outcomes, patient satisfaction, access to care and mixed results on cost-effectiveness. Future research evaluating NLCs needs to adopt a standardised structure to provide rigorous evaluations that can rationalise further efforts to set up community based nurse-led clinical services.